Desmin Modulates Muscle Cell Adhesion and Migration - Hakibilen, Coralie; Delort, Florence; Daher, Marie-Thérèse; Joanne, Pierre; Cabet, Eva; Cardoso, Olivier; Bourgois-Rocha, Fany; Tian, Cuixia; Rivas, Eloy; Madruga, Marcos; Ferreiro, Ana; Lilienbaum, Alain; et al. (Frontiers in Cell and Developmental Biology, 2022)
Cellular adhesion and migration are key functions that are disrupted in numerous diseases. We report that desmin, a type-III muscle-specific intermediate filament, is a novel cell adhesion regulator. Expression of p.R406W mutant desmin, identified in patients with desmin-related myopathy, modified focal adhesion area and expression of adhesion-signaling genes in myogenic C2C12 cells. Satellite cells extracted from desmin-knock-out (DesKO) and desmin-knock-in-p.R405W (DesKI-R405W) mice were less adhesive and migrated faster than those from wild-type mice. Moreover, we observed mislocalized and aggregated vinculin, a key component of cell adhesion, in DesKO and DesKI-R405W muscles. Vinculin expression was also increased in desmin-related myopathy patient muscles. Together, our results establish a novel role for desmin in cell-matrix adhesion, an essential process for strength transmission, satellite cell migration and muscle regeneration. Our study links the patho-physiological mechanisms of desminopathies to adhesion/migration defects, and may lead to new cellular targets for novel therapeutic approaches.